UJI AKTIVITAS PROTEASE GETAH LABU SIAM DAN TALAS SERTA PERBANDINGANNYA TERHADAP GETAH PEPAYA - Ratnayani, Ketut; Juwarni, A. A. Ayu Septri; Laksmiwati, A. A. I. A. Mayun; Sri Panca Dewi, I G. A. Kunti (Jurnal Kimia (Journal of Chemistry), 2015)
Papaya ( Carica papaya L.) latex has been used commercially as a protease (papain) sources. However it can cause itchy on the skin. Some other latex plants that can cause itchy were taro and chayote.  They were strongly predicted to have protease components. This research aimed to determine protease activity of plants latex of taro ( Xantosoma sagittifolium (L.) Schott and chayote ( Sechium edule (Jacq.) Sw.). The protease activity of these latex then were compared to the protease activity of papaya latex. Latex of papaya and taro were collected from fruit, while latex of chayote was collected from corm. The assay of protease activity was based on spectrofotomeric methods (Anson’s method) using casein as substrat. The result of protease activity assay showed that taro and chayote latex positively contains protease but their protease activities were less than papaya latex which were 0.0123 U/mL and 0.0264 U/mL respectively. It can be concluded that taro and chayote latex were potentially used as alternative protease sources. The protease activity ratio of taro latex to papaya was 1: 74.75 and the ratio of chayote latex to papaya latex was 1: 34.82.
Keywords: chayote latex, taro latex, papaya latex, protease